A Proposal for the Description of Individual Course Units - Barros, João Paulo (2013)
The description of individual course units is here presented as a privileged way to improve course quality by fostering teacher reflection. To that end, the paper presents a structured way to specify the several parts that compose the course unit descriptions. The most important parts are made strongly interconnected as a way to maximize coherence and force additional reflection during course design. The paper presents a concrete template that expands the recommendations and course unit data present in the ECTS User’s Guide. Besides including the usual course data, the template guides the course designer towards the specification of several alignments between the data. These alignments make the course unit descriptions self justifying and internally coherent. Additionally,, a grading strategy is briefly presented and the intended learning outcomes are classified according to the European Qualification Framework for Lifelong Learning.